Price and wage setting in Portugal: learning by asking - Fernando Martins (European Central Bank (ECB), 2011)
This paper presents the main findings of a survey conducted on a sample of Portuguese firms. The main aim was to identify some relevant characteristics about the dynamics of prices and wages in Portugal. The most important conclusions are: i) changes to wages are more synchronized than changes to prices; ii) most wages are defined using inflation as a yardstick, even though there are no formal rules; iii) the wages of most workers are defined in terms of sector-related collective agreements; iv) a considerable proportion of workers receive wages above those been agreed under the collective agreement; v) firms make frequent use of other mechanisms to cut payroll costs as a way of overcoming the restrictions imposed by downward nominal wage rigidity.
Keywords: D21; E30; J31; 330; indexation; institutions; price rigidity; survey data; wage rigidity